The Differences Of Student's Mathematics Ability Using The Whatsapp Group And Classroom Platform During Pandemic Covid-19 - Agustin, Susi; Sari, Dira Puspita (Lembaga Layanan Pendidikan Tinggi Wilayah I Sumatra Utara (LLDikti I), 2021)
The purpose of this study was to determine the differences in students' mathematical abilities using the WhatsApp group and classroom platforms during the Covid-19 pandemic in class VIII of SMP Negeri 2 Hinai. This research method is to use quasi-experimental research. The number of samples in this study were 60 students divided into 2 class groups, namely the experimental class 1 which was taught using WhatsApp group, and the experimental class 2 which was taught using classroom. The data collection instruments were in the form of tests of students' mathematical understanding abilities before and after being given treatment (pretest and posttest). Based on the results of hypothesis testing with the t test technique, the value of t count> t table is 2.16> 2.04 so it can be concluded that there are differences in students' mathematical abilities using the WhatsApp group platform and classrooms during the Covid-19 pandemic in class VIII SMP. Negeri 2 Hinai. Students 'mathematical abilities using the WhatsApp group platform are superior to students' mathematical abilities using classroom.